If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -10r = 25 Reorder the terms: -10r + 5t = 25 Solving -10r + 5t = 25 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-5t' to each side of the equation. -10r + 5t + -5t = 25 + -5t Combine like terms: 5t + -5t = 0 -10r + 0 = 25 + -5t -10r = 25 + -5t Divide each side by '-10'. r = -2.5 + 0.5t Simplifying r = -2.5 + 0.5t
| 3x-9-2x=-21 | | 4n(2n^2)=0 | | 23x-9-12x+4=22x-9-11x+17 | | 10x-2(x+3)=4(2x+3) | | 2u^2(4u)=0 | | -1-1*(y-3(y-4*(y-5)))=11*(12-2y)+y | | 59-4x=14-x | | 2w^2-17w+21= | | 3[4+3(6-4)]= | | 10x+0(1-x)=20x+0(1-x) | | 4-4a=3-6a | | 27a^3b^5/45a^4b^3 | | r-6f^2+1=0 | | 2(y-6)=-2y-4 | | 128v+11r-150r-3r= | | -13-7x=4x-5 | | 200x-0.21=400x+0.51 | | 2x+4x+x=180 | | -8u+5(u-3)=6 | | 3x+(x+8)+x=93 | | m=-1/4(-9,0) | | V=3.14*49*33 | | ln(5x-5)=ln(4x-1) | | 8(4u-1)-12u=1(2u-6) | | c+13=3c+7 | | m=1/4(-9,0) | | V=3.14*6 | | -13-7x=2.5x-5 | | 2c+3=c+8 | | 3y+5y-2y= | | 3x+cosx=6 | | x^2-x/3-1/6=0 |